Some Epidemiologic Aspects of Common Warts in Rural Primary School Children. (8th December 2013) - Kasim, Khaled; Amer, Soliman; Mosaad, Mohamed; Abdel-Wahed, Alaa; Allam, Hazem
Abstract : Cutaneous warts are common in children worldwide, although the prevalence figures are conflicting. There are few publications on that issue, particularly in rural Egypt. The present cross-sectional study aimed to assess the prevalence of warts of hands in rural primary school children and to examine some risk factors associated with warts in these children. The study examined 1833 children from 15 rural primary schools in Dakahlia governorate, Egypt, for the presence of warts. Data about sociodemographic, lifestyle, and environmental factors were collected. Prevalence of warts was estimated. Appropriate statistical analyses including multivariate logistic regression were done. The prevalence of warts of hands in the studied children was 2.3% (1.3–3.3%) with no significant sex difference. The risk of warts increased significantly in children reported swimming in Nile channels (adjusted odds ratio (OR) = 5.6; 95% confidence interval (CI) = 2.9–10.6) and child labor (adjusted OR = 4.5; 95% CI = 2.3–8.8). A ninety percent risk reduction was observed in children with educated parents. The study findings demonstrated a significant increase in the risk of warts among rural children reported swimming in Nile channels and child labor. Parents' education, on the other hand, was found to play an important role in risk reduction.